2021
DOI: 10.1002/jdd.12597
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and its impact on dental students: A multi‐institutional survey

Abstract: Purpose/objectives To investigate dental students’ perceptions and concerns regarding the COVID‐19 pandemic, their coping strategies and support resources, and their perceived stress levels. Methods A customized 19‐item survey and the perceived stress scale (PSS) were applied to undergraduate dental students from the US, Spain, Ireland, Chile, India, and Brazil between April 10 and July 5, 2020. Linear modeling and mediation analysis were used to explore the relationships among demographics, stressors, coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 19 publications
(34 reference statements)
2
57
1
1
Order By: Relevance
“…On the other hand, Yildirim et al (20) found higher anxiety levels in female and clinical dental students. Also, these results were similar to those of an international study conducted by Klassen et al (21). They found that those dental students who worried about their academic progress, also referred higher anxiety levels.…”
Section: Related Findingssupporting
confidence: 90%
“…On the other hand, Yildirim et al (20) found higher anxiety levels in female and clinical dental students. Also, these results were similar to those of an international study conducted by Klassen et al (21). They found that those dental students who worried about their academic progress, also referred higher anxiety levels.…”
Section: Related Findingssupporting
confidence: 90%
“…For this reason, in this study, when specific elements related to the pandemic were asked, statistically significant differences were found in the bivariate analyses. For students, this meant new academic responsibilities mediated by remote and virtual strategies and some additional financial burdens in the context of great difficulties, among other circumstances [ 14 , 29 ]. In professionals, new labor adaptations were created, and this caused a decrease in working hours and even suspended face-to-face clinical activities [ 8 , 9 , 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on mental health topics related to the pandemic among dental staff in Latin America and the Caribbean is scarce. A scientific literature exploration reveals some published studies and gray literature carried out in specific settings and with specific samples [ 27 , 28 ], as well as multicenter studies in dental students in Latin American countries (Brazil and Chile) [ 29 ]. Hence, the extent of scientific research in this region should be increased through studies with methodologies targeted at specific problems and by analyzing the determining factors of physical, mental, and psychosocial health indicators.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of clinical education, students reported that they had to adapt to changes and didactic learning; others indicated that at least one of their courses moved to virtual mode. Although 51.8% perceived some difficulties during virtual education, 48.3% perceived that faculty were prepared for the online transition [62]. Some students reported feeling stress about the risk of infection and returning to clinical classes and patient contact [63].…”
Section: Et Al [58]mentioning
confidence: 99%
“…In this matter, faculty support is needed to help in the transition and concerns about academic progress and stress levels [62].…”
Section: Et Al [58]mentioning
confidence: 99%